We have to prove that (3 sec x+3 cos x)(3 sec x - 3 cos x) = 9[(tan x)^2 + (sin x)^2]

(3 sec x+3 cos x)(3 sec x - 3 cos x)

=> 9[ (1/cos x) + cos x][ (1/cos x) - cos x]

=> 9[ (1/cos x)^2 - (cos x)^2]

=> 9[ (((cos x)^2 + (sin x)^2)/cos x)^2 - (cos x)^2]

=> 9[ ((cos x)^2/(cos x)^2 + (sin x)^2/cos x)^2 - (cos x)^2]

=> 9[ 1 + (tan x)^2 - (cos x)^2]

=> 9[ (tan x)^2 + (sin x)^2]

**This proves : (3 sec x+3 cos x)(3 sec x - 3 cos x) = 9[(tan x)^2 + (sin x)^2]**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.